2017
DOI: 10.1371/journal.pone.0172712
|View full text |Cite
|
Sign up to set email alerts
|

Development of a keratinase activity assay using recombinant chicken feather keratin substrates

Abstract: Poultry feathers consist mainly of the protein keratin, which is rich in β-pleated sheets and consequently resistant to proteolysis. Although many keratinases have been identified, the reasons for their substrate specificity towards β-keratin remain unclear due to difficulties in preparing a soluble feather keratin substrate for use in activity assays. In the present study, we overexpressed Gallus gallus chromosomes 2 and 27 β-keratin-encoding genes in Escherichia coli, purified denatured recombinant proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“…When added to reaction mixtures containing WCEs derived from F. islandicum AW-1 cells, these enzymes accelerated and/or enhanced the degradation of native chicken feathers, resulting in the release of free amino acids from feather keratin (Fig. 4), which was in accordance with the previous results (Lee et al, 2015a;Jin et al, 2017). It could be speculated that peptide fragments produced from feathers by activated cytoplasmic endo-and exoproteases might act as transcription triggering factors or signalling molecules via peptide transporters to promote feather decomposition and utilization.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…When added to reaction mixtures containing WCEs derived from F. islandicum AW-1 cells, these enzymes accelerated and/or enhanced the degradation of native chicken feathers, resulting in the release of free amino acids from feather keratin (Fig. 4), which was in accordance with the previous results (Lee et al, 2015a;Jin et al, 2017). It could be speculated that peptide fragments produced from feathers by activated cytoplasmic endo-and exoproteases might act as transcription triggering factors or signalling molecules via peptide transporters to promote feather decomposition and utilization.…”
Section: Discussionsupporting
confidence: 91%
“…In the light of this, the extremely thermophilic bacterium F. islandicum AW‐1, which can degrade chicken feathers completely within 48 h at 70ºC (Nam et al , ), would be an excellent model system to investigate the mechanism of keratinolysis under anaerobic conditions, because this bacterium belongs to the order of Thermotogales, which is the most ancient form of bacteria. Intriguingly, our previous LC‐MS/MS analysis revealed that unlike other general serine proteases such as trypsin and proteinase K, F. islandicum AW‐1 proteases exhibited a distinct substrate specificity towards feather keratin (Jin et al , ). Unlike aerobic superficial dermatophytes such as M. canis and T. rubrum that secrete the highly conserved set of S3 and M3 endoproteases (Monod, ; Sriranganadane et al , ), anaerobic F. islandicum AW‐1 appears to degrade native feathers via direct cellular adhesion to the substrate by expressing membrane‐bound proteases (Nam et al , ).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…[45] and Streptomyces pactum [49]. The initial step in keratin degradation catalyze by disulfide reductase has also been reported by other researchers [50][51][52][53]. Reduction of disulfide bonds changes the conformation of amino acids in β-sheet of keratin rendering different hydrolytic sites for proteolytic attack by keratinase [16,54].…”
Section: Mechanism Of Feather Degradationmentioning
confidence: 60%